TRPC Channels in the SOCE Scenario - Lopez, Jose J. (Cells, 2020)
Transient receptor potential (TRP) proteins form non-selective Ca(2+) permeable channels that contribute to the modulation of a number of physiological functions in a variety of cell types. Since the identification of TRP proteins in Drosophila, it is well known that these channels are activated by stimuli that induce PIP(2) hydrolysis. The canonical TRP (TRPC) channels have long been suggested to be constituents of the store-operated Ca(2+) (SOC) channels; however, none of the TRPC channels generate Ca(2+) currents that resemble I(CRAC). STIM1 and Orai1 have been identified as the components of the Ca(2+) release-activated Ca(2+) (CRAC) channels and there is a body of evidence supporting that STIM1 is able to gate Orai1 and TRPC1 in order to mediate non-selective cation currents named I(SOC). STIM1 has been found to interact to and activate Orai1 and TRPC1 by different mechanisms and the involvement of TRPC1 in store-operated Ca(2+) entry requires both STIM1 and Orai1. In addition to the participation of TRPC1 in the I(SOC) currents, TRPC1 and other TRPC proteins might play a relevant role modulating Orai1 channel function. This review summarizes the functional role of TRPC channels in the STIM1–Orai1 scenario.